Product characterization from catalytic liquefaction of empty palm fruit bunch (EPFB) in near and supercritical water - Saidina Amin, Nor Aishah; Mat, Ramli; Haron, Roslindawati; Javaid, Akhtar; Soo, Kim Kuang (Faculty of Chemical and Natural Resource Engineering, 2009)
Catalytic performance and suitable biomass to water ratio that supported higher EPFB conversion, liquid hydrocarbons yield and lignin degradations were screened for EPFB liquefaction under subcritical conditions operating at 270oC and 20 bars for 20 minutes. Analytical results indicate that maximum of 68 wt% liquids were produced along with 72.4 wt% EPFB mass conversion and 65.6 wt% lignin degradation under 1.0 MK2CO3/2:10 (biomass/water) conditions. In comparison, the experiments that were performed in the absence of alkalis yielded only 30.4 wt% liquids, converted 36 wt% EPFB and degraded 24.3 wt% lignin. Furthermore, biomass to water ratios >2:10 decreased both solid mass conversion and liquid hydrocarbons’ yield. The reactivity of the alkalis was in the order of K2CO3 > KOH > NaOH. The liquid compositions were dominantly phenols and esters; the highest value of phenol (60.1 wt% of liquid yield) was achieved in the case of K2CO3 (1.0 M) with 5 g EPFB/25 ml water ratio while 1.0 MNaOH yielded maximum esters (86.4 wt% of liquid yield). The alkali promoted process assisted with hot water treatments seemed promising for production of bio-oils from EPFB.